Modelo de gestão de portfólio de projetos em organizações sem fins lucrativos: um estudo exploratório em uma associação médica de especialidade - Lacerda, Fabrício Martins (2013)
Nonprofit organizations have increased their participation in society and pursued for tools that facilitate the management, leadership and control of their work routines in the knowledge area of management. These social actors also adopt strategic planning techniques, making the acceptance of the methodology of project portfolio management a natural consequence. Notwithstanding, there is an apparent lack of interaction between social science students and authors of project management methodology which can contribute to an ineffective realization of this relationship. Thus, this study is focused on the project portfolio management of nonprofit organizations, especially in Medical Specialty Societies, and aims to propose a model adapted for the context of project portfolio management in Medical Specialty Societies. In this sense, the research question was defined as "how to manage project portfolios in the area of Medical Specialty Society?". To answer this question it was necessary to identify models from the literature in question; analyze the models by presenting a comparative synthesis and relating the common dimensions between them; verify the applicability of the models in the context of Medical Specialty Society, as well as identify the dimensions of project portfolio management that apply to such organizations. For this, an exploratory case study was conducted as strategy research, qualitative evaluation method and sources of evidence gathered through participant observation, documents analysis, files registering and interviews. To triangular analysis of the data, we adopted the general strategy of the case description and analytical technique of standardization adequacy. Following it was conducted a comparison of the procedures adopted in the case study with the dimensions suggested by projects portfolio management models identified in the literature and summarized in the conceptual model. It was possible to verify the applicability of the dimensions, suggest new elements, words and nomenclatures, highlighting to a new dimension. Thus, the main objective of the study achieved with the proposition of a project portfolio management model adapted to the context of a Medical Specialty Society.